Structure and thermodynamic stability of UTa3O10, a U(v)-bearing compound. Issue 47 (15th September 2016) - Guo, Xiaofeng; Lipp, Christian; Tiferet, Eitan; Lanzirotti, Antonio; Newville, Matthew; Engelhard, Mark H.; Wu, Di; Ilton, Eugene S.; Sutton, Stephen R.; Xu, Hongwu; Burns, Peter C.; Navrotsky, Alexandra
Abstract : We report the crystallography, structure, and thermodynamics of a new U(V)-containing compound, UTa3 O10 . Abstract : Heating a mixture of uranyl(vi ) nitrate and tantalum(v ) oxide in the molar ratio of 2 : 3 to 1400 °C resulted in the formation of a new compound, UTa3 O10 . The honey colored to yellow brown crystals of UTa3 O10 crystallize in an orthorhombic structure with the space group Fddd (no. 70), lattice parameters a = 7.3947(1), b = 12.7599(2), c = 15.8156(2) Å, and Z = 8. Vertex sharing [TaO6 ] 7− octahedra of two crystallographically distinct Ta cations form a three dimensional tantalate framework. Within this framework, six membered rings of [TaO6 ] 7− octahedra are formed within the (001) plane. The center of these rings is occupied by the uranyl cations [UO2 ] +, with an oxidation state of +5 for uranium. The pentavalence of U and Ta was confirmed by X-ray photoelectron spectroscopy and X-ray adsorption spectroscopy. The enthalpy of formation of UTa3 O10 from Ta2 O5, β-U3 O7, and U3 O8 has been determined to be 13.1 ± 18.1 kJ mol −1 using high temperature oxide melt solution calorimetry with sodium molybdate as the solvent at 700 °C. The close to zero enthalpy of formation of UTa3 O10 can be explained by closely balanced structural stabilizing and destabilizing factors, which may also apply to other UM3 O10 compounds.